A brief assessment for selecting communication modalities for individuals with Autism Spectrum Disorders. Issue 1 (2nd January 2016) - LaRue, Robert H.; Pepa, Lauren; Delmolino, Lara; Sloman, Kimberly N.; Fiske, Kate; Hansford, Amy; Liebross, Stacey; Weiss, Mary Jane
Abstract: Individuals with autism spectrum disorders (ASD) have impairments in their ability to communicate with others. Estimates indicate that about 25–50% of children with ASD are nonvocal. To address these deficits, a number of augmentative and alternative communication strategies have emerged. Commonly used communication responses have included vocal speech, picture exchange, and manual signs. While these communication strategies have all been shown to be effective in specific clinical instances, the selection of communication topography has generally been based on philosophical preference, rather than on empirical analyses. Relatively little research has evaluated procedures to determine which modality represents a "best fit" with individual learning styles. The purpose of the current investigation was to design a brief assessment model to evaluate the rate of acquisition and preference for different communication modalities for three individuals with ASD. The results show that participants acquired different modalities of communication at different rates and displayed clear preferences for different styles of communication. These findings suggest that this procedure may help to empirically determine which communication system represents a best fit for individual learners.